"I Think I Can . . . Maybe I Can . . . I Can't": Social Work Women and Local Elected Office. Issue 2 (7th February 2018) - Meehan, Patrick
Abstract: If women are more interested in running for office, it should be observable in MSW students. Not only are the majority of students women, but they have experienced a dramatic change in political fortunes within the last year. However, the 2016 election may be leading women to doubt their qualifications to run. Using survey data from 545 MSW students and 200 law students, this study considers how interested women are in running for office and what barriers they perceive to doing so. Results suggest that women in MSW programs were significantly more interested in running for local office (city council, school board, county commission) than women in law school. At the same time, women in MSW programs were significantly more likely to doubt their qualifications to run for local office, which significantly decreased their interest in running. Content analysis revealed that women felt this way because they did not believe they had the knowledge and experience to run for local office. These results suggest that field placements in political offices might be a way to provide women in MSW programs with knowledge and experience that increases their sense of qualification to run for local office.